1996
DOI: 10.1046/j.1365-2249.1996.d01-809.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of type 1 and type 2 cytokine production profile in physiologic and pathologic human pregnancy

Abstract: SUMMARYAntigen-and mitogen-stimulated cytokine production by peripheral blood mononuclear cells (PBMC) of 50 pregnant women and 31 age-and sex-matched non-pregnant controls were analysed to determine whether changes in cytokine production occur during normal and pathologic human gestation. The pregnant women, consecutively enrolled during a 3-month period, were undergoing a normal, nonpathologic pregnancy at the time of entry into the study, and underwent ultrasound examination to ascertain the exact week of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
380
5
19

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 566 publications
(431 citation statements)
references
References 34 publications
24
380
5
19
Order By: Relevance
“…IFN␥ production by peripheral lymphocytes in very early pregnancy is higher in normal women compared with women with recurrent miscarriage. 42 By contrast, IL-10 is known to be an antiinflammatory cytokine, 45 and as shown in our study and others, 46,47 high levels of IL-10 are associated with successful outcome. We also found that, when the ratios of Th1/Th2 cytokines were calculated, there was a shift towards Th1 cytokines with elevated TNF␣/IL-10 and IFN␥/ IL-10 ratios in patients with TM who subsequently miscarried.…”
Section: Commentsupporting
confidence: 65%
“…IFN␥ production by peripheral lymphocytes in very early pregnancy is higher in normal women compared with women with recurrent miscarriage. 42 By contrast, IL-10 is known to be an antiinflammatory cytokine, 45 and as shown in our study and others, 46,47 high levels of IL-10 are associated with successful outcome. We also found that, when the ratios of Th1/Th2 cytokines were calculated, there was a shift towards Th1 cytokines with elevated TNF␣/IL-10 and IFN␥/ IL-10 ratios in patients with TM who subsequently miscarried.…”
Section: Commentsupporting
confidence: 65%
“…59 This change is considered important for a healthy term pregnancy. 9,10 Although we did not see any overall association with Th2, we did observe lower concentrations of IL-4 and IL-10 with increasing concentrations of MeHg at 28 weeks gestation. In pregnancy, IL-10 is an important immunoregulatory cytokine produced by cytotrophobloasts at the materno-fetal interface acting to maintain the balance between humoral and inflammatory responses.…”
Section: Discussioncontrasting
confidence: 69%
“…2,8 In the second trimester, Th2 cells secrete predominantly anti-inflammatory cytokines including interleukin (IL)-4, IL-5 and IL-10 which, in combination with a reduction in inflammatory Th1 cytokines IL-1β, IL-2 and interferon gamma (IFN)-γ, have been associated with healthy term pregnancy. 9,10 Therefore, specific balance between maternal pro-inflammatory and anti-inflammatory cytokines throughout pregnancy is believed to be critical for the success of a pregnancy and favourable birth outcomes. 11 The normal variation, however, in the magnitude of these immunologic changes during pregnancy has not been fully defined.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that successful pregnancy is a Th2‐related phenomenon 3. To our knowledge, six cases of EPF associated with pregnancy have been reported in the published work.…”
Section: Figurementioning
confidence: 93%
“…In one of ours (case 1), EPF developed after the start of the first pregnancy and relapsed during the second pregnancy. Although further information is needed, these may indicate that pregnancy and EPF are correlated through Th2‐type immune responses 2, 3…”
Section: Figurementioning
confidence: 99%